2017
DOI: 10.1016/j.nepr.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence as a subject of study during the training of nurses and midwives in Catalonia (Spain): A qualitative study

Abstract: a b s t r a c tWhile nurses and midwives are in a unique position to identify and help victims of IPV, since they are often their first point of contact in the healthcare system, they need appropriate training. This study sought to examine the presence of IPV-related contents and the depth to which they are addressed in the bachelor's degree in Nursing and in the Midwifery specialisation programme. The study also explored lecturers' motivations for including IPV in their subjects. The methodology employed was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…This puts them in a crucial position to address IPV from a facility-based perspective. IPV knowledge, attitude, and preparedness are important factors that affect nurses’ and midwives’ capacity to manage clients experiencing IPV [ 17 , 18 ] and are acquired through appropriate preservice and continuing education [ 19 ]. Therefore, evaluating nurses’ and midwives’ current conditions related to IPV knowledge, attitudes, and preparedness is important in determining their capacity to provide IPV care and services.…”
Section: Introductionmentioning
confidence: 99%
“…This puts them in a crucial position to address IPV from a facility-based perspective. IPV knowledge, attitude, and preparedness are important factors that affect nurses’ and midwives’ capacity to manage clients experiencing IPV [ 17 , 18 ] and are acquired through appropriate preservice and continuing education [ 19 ]. Therefore, evaluating nurses’ and midwives’ current conditions related to IPV knowledge, attitudes, and preparedness is important in determining their capacity to provide IPV care and services.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to highlight that prior studies have found specific training programs involving contrasting IPV to be very effective [ 23 ]. Therefore, it is essential to promote training courses in order to encourage a psychosocial management of IPV in all social and health services involved in the prevention and detection of IPV [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, children suffer as both witnesses of violence against their mothers and because they lack the care of their mother, who is unfortunately the victim of the daily violence. In addition to the organizational gaps and the poor training of health service personnel, the invisibility of IPV among operators is attributed to the common cultural power asymmetries [ 26 , 27 , 28 ] that characterize relationships between women and men, in which men wield greater levels of power [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They emphasized the need for violence screening training to students providing healthcare services and considered their presence in related clinical settings necessary for the integration of theoretical and practical knowledge. (12) Despite the high prevalence of domestic violence in various countries, including Iran, very few studies have been conducted on this subject, and given recent findings in Canada showing the students' greater use of social media for learning scientific topics, (13) the present study was conducted to examine the effect of training on the legal aspects of domestic violence against women through social networks on the awareness and attitude of nursing students.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%